Evaluation of the Effectiveness and Cost-Efficiency of Nudging Overdue Car Taxpayers Behavior through Reminder Letters - Wattatham, Sadanon; Chantith, Chaturaphat (Journal of Applied Economics and Management Strategy, 2024)
This research evaluated the effectiveness and cost-efficiency of overdue car tax reminder letters issued by the Songkhla Provincial Administrative Organization (PAO) in 2023. A total of 64,100 reminder letters were sent, and data on overdue vehicle taxes before and after the letters were analyzed using descriptive statistics, including frequency, percentage, and mean. The effectiveness was assessed by comparing the percentage increase in collected overdue taxes with previous studies, employing a t-test for analysis. The efficiency of the letters was determined using the lowest-rated performance score as a coefficient, which measured the letters' ability to prompt tax payments. This coefficient was based on feedback from 104 respondents collected via an online survey through accidental sampling. The economic cost-efficiency was evaluated using the benefit-cost ratio (B/C Ratio). The study found that the reminder letters effectively prompted car owners in the Songkhla PAO to pay overdue taxes, achieving a 5.63% higher success rate than previous studies. This number reduced overdue car taxes by over 29.32 million baht, with a payment stimulus coefficient of 0.3, leading to an additional 1.81 million baht collected due to the effectiveness of the letters. The cost-efficiency analysis revealed that the letters were highly cost-effective, generating 7.49 times more revenue than the expenses incurred. The study recommended enhancing the credibility of the reminder letter system and incorporating technology. As well as studying the decline of overdue car tax through the effectiveness of behavior nudging with tax reminder letters.